PENGARUH KEPUASAN KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI NEGERI SIPIL (PNS) (Studi Pada Kantor Pertanahan Kabupaten Tanah Laut) - Mahrita; Ahmad Alim Bachri; Maya Sari Dewi (Universitas Lambung Mangkurat, 2015)
This study aimed to analyze the effect of job satisfaction (X1) and Transformational Leadership Style (X2) as independent variables either simultaneously or partially on Organizational Citizenship Behavior (Y) as the dependent variable in the Civil Service Tanah Laut District Land Office. This research method using a questionnaire to 32 employees in Tanah Laut District Land Office as a sample. Sampling technique used is the Census methods. Variable measurement technique Likert scale with a weight scale from 1 to 5. To analyze the influence of variables Job Satisfaction and Transformational Leadership Style on Organizational Citizenship Behavior (Y) using multiple linear regression statistical techniques. The results showed that the variables job satisfaction and Transformational Leadership Style jointly significant effect on Organizational Citizenship Behavior PNS Tanah Laut District Land Office. Variables Job Satisfaction partially not significant effect on Organizational Citizenship Behavior PNS Tanah Laut District Land Office. Variable Transformational Leadership Style partially not significant effect on Organizational Citizenship Behavior PNS Tanah Laut District Land Office.